Probabilistic Approach to Reliability-Based Optimum Structural Design - A. Brandt; S. Jendo; W. Marks (Engineering Transactions)
In the paper foundations are given for the design of structures and structural optimization, based on the theory of probability. In this approach, loads, dimensions and material properties are considered as random values. The safety of the structure should be assured and the constraints should be satisfied with acceptable probabilities. A programming method is proposed with random constraints to reduce the probabilistic optimization problem to a deterministic one. The theoretical considerations are applied to an example in which optima! dimensions of a frame box beam are determined.